ANALISIS PENGARUH KUALITAS SUMBER DAYA MANUSIA TERHADAP KINERJA PENGELOLAAN KEUANGAN DAERAH DI PROVINSI KALIMANTAN BARAT - B61111004, Lely Hadiawati (Jurnal Ekonomi Daerah (JEDA), 2015)
ABSTRACT This research aims to know and to analyze the influence of the apparatus resources to the performance of the district financial management in Kalimantan Barat during the year 2008 - 2012. The research method used is qualitative research method. Samples of the research cover of four districts, those are Ketapang, Melawi, Kubu Raya and Kayong Utara. The analysis instruments of the financial management performance measurer use the Ratio of Degree of Fiscal Decentralization, Ratio of Regional Financial Independence, Ratio of Effectiveness, Ratio of Activity and Ratio of Revenue Growth. In addition, the influence of the apparatus resource to the financial management performance uses simple regression. Results of the research in period of 2008 -2012 show that the ratios of degree of fiscal decentralization and the Regional Financial Independence of new district are relatively very low, those are less than 10%. Except Melawi district, the Ratio of effectiveness in Bengkayang, Kubu Raya and North Kayong are very effective. The Ratio of activity shows that the allocation of direct expenditure is smaller than indirect expenditures. The ratio of district original revenue growth (PAD) and the District Revenue Growth are fluctuated and only North Kayong district which has a positive growth trend. The analysis results of the influence of apparatus resources which are assumed to the higher education on the performance of financial management show that the higher education only influences the ratio of Effectiveness.